Islam and the Arts: A Humanities Study of Islamic Calligraphy, Music, and Architecture - Rizki Rahmatillah; Inayatillah Inayatillah (Global Education Journal, 2026)
Art in Islamic civilization is often reduced to a dichotomy of haram and halal, whereas the classical Islamic intellectual tradition views beauty as a manifestation of monotheism that unites theological, aesthetic, and human dimensions. Academic studies that integrate Islamic calligraphy, music, and architecture within a single humanities framework are still very limited, so the understanding of Islamic art tends to be fragmented between branches. This research aims to analyze how the three branches of art, integratively, represent monotheism as a transcendental aesthetic principle that unites the spiritual, humanistic, and civilizational dimensions in Islamic art. The research uses the library research method with a philosophical-humanistic approach, through eight stages, namely problem identification, literature search, literature selection, data extraction, content analysis, philosophical interpretation, synthesis, and conclusion drawn, with the analytical framework of aesthetic theory of Seyyed Hossein Nasr, Ismail Raji al-Faruqi, and Titus Burckhardt. The results of the study show that calligraphy represents monotheism textually-visually, music represents it auditorially-spiritually through the sama' and qasidah traditions, and architecture represents it spatially through the geometry and light of the mosque, so that the three meet at the same generative point, namely monotheism. This study concludes that the integrative humanities approach makes a new theoretical contribution to understanding Islamic art as a coherent monotheistic aesthetic system, as well as relevant for strengthening the identity of contemporary Islamic civilization.